2019
DOI: 10.1186/s12915-019-0659-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological and RNA regulatory function of MOV10 in mammalian germ cells

Abstract: Background RNA regulation by RNA-binding proteins (RBPs) involve extremely complicated mechanisms. MOV10 and MOV10L1 are two homologous RNA helicases implicated in distinct intracellular pathways. MOV10L1 participates specifically in Piwi-interacting RNA (piRNA) biogenesis and protects mouse male fertility. In contrast, the functional complexity of MOV10 remains incompletely understood, and its role in the mammalian germline is unknown. Here, we report a study of the biological and molecular funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 99 publications
(134 reference statements)
0
39
0
1
Order By: Relevance
“…In addition to PTGDS, MOV10L1, and DEUP1 were also reported to be specifically expressed in testicular tissue [ 19 , 20 ]. The expressions of MOV10L1 and DEUP1 between the two chicken groups were extremely different, and they were in the top five ranked by FDR values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to PTGDS, MOV10L1, and DEUP1 were also reported to be specifically expressed in testicular tissue [ 19 , 20 ]. The expressions of MOV10L1 and DEUP1 between the two chicken groups were extremely different, and they were in the top five ranked by FDR values.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of MOV10L1 and DEUP1 between the two chicken groups were extremely different, and they were in the top five ranked by FDR values. MOV10L1 participates in piwi-interacting RNA biogenesis and protects mouse male fertility, enhancing the proliferation capacities of spermatogonial progenitor cells [ 19 ]. A study on human tissue-specific expression reported that DEUP1 was specifically highly expressed in testicular tissues, indicating DEUP1 played an important role in male fertility [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the non-canonical pathway, pre-miRNAs are formed by splicing, debranching, and trimming of short introns without Drosha processing (74). In this process to form pre-miRNAs, MOV10 typically binds splicing factors, such as SRSF1 and DDX5 (68,75), forming a splicing complex, which completes the pre-mRNA and pri-miRNA splicing process after binding intronic regions (Figure 2).…”
Section: Mov10 Mediates Inhibition Of Rna Viruses Via Mirna Pathwaysmentioning
confidence: 99%
“…Um importante mecanismo de ação dos lncRNAs é a sua capacidade de interação com proteínas e, uma vez identificadas essas interações, é possível compreender as potenciais funções dos lncRNAs(ZHANG et al, 2019a). Para tal análise, foi utilizado o banco de dados NPInter 4.0, que possui interações de ncRNAs validadas experimentalmente(TENG et al, 2020), encontrando interação do RP11-1082A3.1 com 6 proteínas (Tabela 2).As proteínas identificadas até o momento como parceiras de interação do lncRNA, de acordo com o os bancos de dados utilizados, estão localizadas principalmente no núcleo celular e estão, na Estudo recente demonstrou que a proteína MOV10 pode ser encontrada tanto no núcleo quanto no citoplasma de células germinativas masculinas primordiais, apresentando um papel fundamental na determinação de linhagem e na proliferação de células progenitoras espermatogoniais(FU et al, 2019). Além disso, um outro estudo, em camundongos, mostrou que essa proteína é essencial para o desenvolvimento embrionário e para o desenvolvimento e funcionamento saudável do sistema nervoso central(SKARIAH et al, 2017).…”
unclassified